A Trends in Dietary Supplement Related to Exercise Nutrition - Sowmitha M; Sobhana G (International Journal of Nutritions, 2024)
A product made to address physiological or nutritional demands that might occur during sports activity is called a dietary supplement. It could offer a convenient method for fulfilling specific nutritional needs during exercise, or it could be utilized to prevent or address common nutritional deficiencies experienced by athletes. It is crucial to include the supplement in a thorough plan for the best possible sports nutrition or clinical care of nutritional problems. In addition to ensuring the proper utilization of dietary supplements, effective education emphasizes the significance of achieving optimal nutrition tailored for sports performance. This study explores contemporary trends in dietary supplements within the realm of exercise nutrition. The need for specialized nutritional support rises along with the fitness industry. Our research delves into the latest advancements, examining popular supplements, their efficacy, and the underlying factors driving their adoption. We aim to provide a comprehensive overview of the current landscape, shedding light on emerging patterns that influence choices in exercise- related dietary supplementation. Understanding these trends is crucial for both consumers and health professionals in optimizing nutritional strategies for enhanced exercise performance and overall well-being. Moreover, the landscape of dietary supplements maintains to adapt alongside advancements in exercising science and dietary research. As the call for for specialised support in sports vitamins escalates in the health industry, it turns into imperative to live abreast of emerging developments and innovations. Our study endeavors to bridge this gap by scrutinizing not only the efficacy of popular supplements but also the factors motivating their widespread adoption.
Keywords: Dietary supplements; Exercise Nutrition; Performance Enhancement